41 Cardiovascular Magnetic Resonance Left Ventricular Stroke Volume and Outcome Prediction in Patients with Aortic Stenosis Following Intervention. (3rd June 2016) - Selvendran, Subothini; Aggarwal, Nikhil; Auger, Dominique; Nyktari, Eva; Raphael, Claire; Prasad, Sanjay; Vassiliou, Vass
Abstract : Introduction: Percutaneous transcatheter aortic valve implantation (TAVI) is gaining significant popularity as an alternative to conventional aortic valve replacement surgery for patients with aortic stenosis (AS), especially in high operative risk patients. We investigated outcome prediction using a cohort of patients undergoing TAVI and utilising patient demographic and cardiovascular magnetic resonance (CMR) parameters. Methods: Between 2010–2014, 100 consecutive patients with severe AS scheduled for TAVI underwent CMR. We retrospectively analysed data on a variety of patient demographics to identify any associations with overall mortality. Follow-up was completed using electronic hospital records and data obtained from the National Strategic Office. Kaplan-Meier curves were obtained and compared using the log-rank test. Univariate analysis was used on 20 variables and those significant included in a multivariate Cox regression model. Results: 100 patients (median age 81 years; 55 male) were followed for a median 1349 days. During this period 20 patients died. 12 patients were lost to follow up and were censored for statistical purposes at their last known time being alive. On univariate analysis left ventricular stroke volume (LVSV) and known history of hypertension were associated with survival (Table 1 and Figure 1 ). On multivariable analysis both remained significantly associated with survival [HR=2.997 (95% CI:1.393–6.448, p = 0.005) for history of hypertension and HR=0.983 (95% CI:0.968–0.998, p = 0.031) for 1mL LVSV increase]. Conclusions: In this cohort of elderly AS patients who underwent CMR before TAVI, a lower LV Stroke volume and the presence of hypertension were associated with worse prognosis. LV Stroke Volume appears to be more useful than Left Ventricular Ejection Fraction and Right Ventricular Ejection Fraction. We recommend that it could be routinely assessed in addition to the other parameters already employed in clinical practice.